ANALISIS KONSISTENSI PENERAPAN SISTEM BAGI HASIL DAN PENGEMBANGAN SISTEM PELAYANAN PERBANKAN SYARI‘AH - Qoriah A. Siregar (Fakultas Seni Rupa dan Desain ITB, 2011)
The presence of sharia banks is essentially inseparable from the idea that conventional banking institutions have not been able to mobilize Muslims to the fullest. Differences of opinion on interest banks tend to affect the attitudes of Muslims in Indonesia in the use of banking services. However, Fatwa Commission of the Indonesian Ulema Council (MUI) has recommended the provision of bank interest as usury laws. Development of the fatwa on bank interest provisions of this law will in turn influence people's attitudes towards banking services in general and the public demand for sharia banks in particular. Therefore, Shari'ah banking institutions should be able to improve its operational capabilities and can guarantee that the products on offer are fully in compliance with Shari'ah principles. Muamalat Indonesia (BMI) Branch Bandung offers banking products based profit-sharing system that consists of funds products and financing products. The application-sharing system on the product being offered when analyzed fully in compliance with Shari'ah concept. Based on the survey, the development priorities of service systems BMI Branch Bandung can also be determined. The main priority is the development program associated with an increased factor of credibility and access factors. Thus, BMI Branch Bandung need to do two important things, namely: (1) convince the public that the banking products and services offered in accordance with the concept of Shari'ah and (2) expand the reach of network services to all parts of the city of Bandung making it easier for people to obtain service. Keywords: Shariah banking, conventional banking, profit sharing, interest.